Análisis del prototipo de máquina tuneladora con integración de membrana en su estructura para estudios presiométricos en la fase de excavación (2019)
"This work focuses on the case of the expansion of the cylindrical cavity under pressure conditions in a radial field analyzed in a biaxial space with vertical and horizontal loads. These loads were imposed thanks to the soil itself and a vertical confinement system. We tried to test the effectiveness of the prototype to calculate mechanical parameters of the soil and its possible implementation, in an analog, to a tunneling machine that contains in its structure a membrane capable of performing pressure tests during the excavation process of an underground work. Presiometric curves were obtained that represent in the behavior of the soil at the application of pressure. It was concluded that the prototype length of the tunneling machine does not affect the pressure modulus or the behavior of the soil." -- Tomado del Formato de Documento de Grado